2012
DOI: 10.1111/j.1600-6143.2011.03766.x
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Anticytomegalovirus Drug Resistance Among D+R− Kidney Transplant Recipients Receiving Preemptive Therapy

Abstract: † These authors contributed equally to this work.Anti-cytomegalovirus (CMV) prophylaxis is recommended in D+R− kidney transplant recipients (KTR), but is associated with a theoretical increased risk of developing anti-CMV drug resistance. This hypothesis was retested in this study by comparing 32 D+R− KTR who received 3 months prophylaxis (valganciclovir) with 80 D+R− KTR who received preemptive treatment. The incidence of CMV infections was higher in the preemptive group than in the prophylactic group (60% vs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 34 publications
(54 reference statements)
4
66
0
2
Order By: Relevance
“…Despite this, treatment duration to obtain absence of CMV replication was shorter during LOD compared with EOD (p < 0.0001). We previously reported that peak viral load and treatment failure were risk factors for antiviral drug resistance during preemptive therapy (25). In this study, we observed that antiviral drug resistance occurred less frequently during LOD than EOD (11% vs. 58.5%, p = 0.008).…”
Section: Resultssupporting
confidence: 50%
See 1 more Smart Citation
“…Despite this, treatment duration to obtain absence of CMV replication was shorter during LOD compared with EOD (p < 0.0001). We previously reported that peak viral load and treatment failure were risk factors for antiviral drug resistance during preemptive therapy (25). In this study, we observed that antiviral drug resistance occurred less frequently during LOD than EOD (11% vs. 58.5%, p = 0.008).…”
Section: Resultssupporting
confidence: 50%
“…During the virological monitoring of CMV disease, the assay was performed once a week until two consecutive negative CMV DNAemia QNATs occurred. Antiviral drug resistance was suspected when persistent viral replication was observed after >2 weeks of appropriate antiviral therapy and was confirmed by fulllength sequencing of the UL97 and UL54 genes (25), performed at the French National Cytomegalovirus Reference Center (Limoges, France). Sequences were compared with the AD169 reference sequence using the Gene Librarian 3.2 software (Visible Genetics Inc., Siemens, France) (26,27).…”
Section: Monitoringmentioning
confidence: 99%
“…Some studies showed a marked benefit of the preemptive approach in Dþ/RÀ patients (28,29), although recent studies have shown a similar or even higher incidence of CMV diseases compared to the use of antiviral prophylaxis (9,30). In a French study, 80 Dþ/RÀ kidney transplant recipients followed preemptively were compared to a historical cohort of 32 Dþ/RÀ patients who received antiviral prophylaxis (30).…”
Section: Impact Of CMV Preventionmentioning
confidence: 99%
“…Finally, we used two different rather diverse approaches to define treatment failure and found consistent results for our main finding. However, currently there is no consensus on how to define treatment failure in CMV infection and the definitions vary by as much as persistence of viremia from 2 to 8 weeks after initiation of treatment (8,22,23). In order to optimize guidelines on how to interpret evolution of CMV viral load during course of treatment, more evidence variation in clinical and virological (i.e.…”
Section: Discussionmentioning
confidence: 99%